2019
DOI: 10.1038/s41598-018-37581-9
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of timeseries data reveals changes in 3D segmental coordination of balance in response to prosthetic ankle power on ramps

Abstract: Active ankle-foot prostheses generate mechanical power during the push-off phase of gait, which can offer advantages over passive prostheses. However, these benefits manifest primarily in joint kinetics (e.g., joint work) and energetics (e.g., metabolic cost) rather than balance (whole-body angular momentum, H), and are typically constrained to push-off. The purpose of this study was to analyze differences between active and passive prostheses and non-amputees in coordination of balance throughout gait on ramp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
“…Studies that explicitly stated limitations or confounders were just over two-thirds of the total (Table 2),. 13,14,19–22,24,28–56,71,74,76,77,80–95,108,109,115–132,140–145,147–165,169–180,182–184,188–191,193–198 The most commonly mentioned limitation was small sample size, 20,22,24,28,29,32,33,35,37,39,40,42,45,47,52,54-57,74,80,82,86,87,89,93,95,109,118,119,121,123,126,129,141,143,145,148,149,154-159,161,164,169,172,183,198 followed by generalizability issues, 14,19-21,34,38,41,42,44,52-56,80,81,87,89,109,127-130,142,148,151,155,156,162,171,175-177,184,188,189,191,193,196 recall bias, 14,148,150,157,171,173,182,184 heterogeneous groups, 29,42,54,89,142,174,176,177 homogenous groups, 21,38,39,44,45,91,164 and convenience samples. 14,161,176,177,196…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the first hypothesis, a two-way repeated-measures analysis of variance (ANOVA) was conducted on the standing balance outcomes (COPrms and V-GRFa) to assess the main and interaction effects of stiffness and the eyes-open/eyes-closed (i.e., vision) conditions. For gait data, a one-dimension statistical parametric mapping (SPM) 44 analysis was used to identify regional differences in instantaneous kinetic and kinematic data between the three stiffness conditions (Firm, Medium, and Soft) across the entire gait cycle for each walking speed separately. The critical threshold for the SPM comparison was determined to be 5% ( α = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…As normality was violated, the non-parametric SPM versions of the ANOVA (three strategies) and t-tests (two strategies) were used [70,71]. Post-hoc pairwise comparisons by SPM were only performed on regions of interest indicated by the SPM-ANOVA [72,73]. In line with recent recommendations [74], the aim of applying SPM was to exploratively analyze where the time series tended to differ, to help with the qualitative description of the strategies.…”
Section: Statisticsmentioning
confidence: 99%